2023
DOI: 10.7717/peerj.15742
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbances and the daytime activity of sympatric otters along equatorial Amazonian rivers

Abstract: Background Previous studies suggest coexistence between sympatric neotropical (Lontra longicaudis) and giant otters (Pteronura brasiliensis) maybe facilitated by temporal and spatial differences in activity. Yet, to date there has been no systematic evaluation of activity of these species in sympatry. Here we use extensive multi-year field data to compare temporal and spatial patterns in the diurnal activity of sympatric giant and neotropical otters to answer three questions: Do temporal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Overall, neotropical otters tended to leave later in the morning and enter earlier in the afternoon compared with giant otters. A previous study quantifying river based activity found no evidence of direct interactions between giant and neotropical otters ( Norris & Michalski, 2023 ). Indeed, Norris & Michalski (2023) found river use by giant and neotropical otters was separated temporally (median time difference 3.0 h) and spatially (median distance between species 12.5 km).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Overall, neotropical otters tended to leave later in the morning and enter earlier in the afternoon compared with giant otters. A previous study quantifying river based activity found no evidence of direct interactions between giant and neotropical otters ( Norris & Michalski, 2023 ). Indeed, Norris & Michalski (2023) found river use by giant and neotropical otters was separated temporally (median time difference 3.0 h) and spatially (median distance between species 12.5 km).…”
Section: Discussionmentioning
confidence: 78%
“…A previous study quantifying river based activity found no evidence of direct interactions between giant and neotropical otters ( Norris & Michalski, 2023 ). Indeed, Norris & Michalski (2023) found river use by giant and neotropical otters was separated temporally (median time difference 3.0 h) and spatially (median distance between species 12.5 km). However, results from this earlier study focused only on daytime activity and did not evaluate nocturnal activity of either species.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations